Iterative Learning Control for Singular Network Control System with Time-Delay and Data Dropout. (July 2020) - Li, Zu-Song; He, Fu-Gui; Li, Shi-Rong
Abstract: Since the object becomes more and more complicated and the existed data dropout and network-introduced time-delay are random and varying in network control system (NCS), the traditional control method is more and more difficult to obtain a good control effect. In this paper, the iterative learning control (ILC) issue for a class of linear continuous singular network control system (SNCS) with time-delay and data dropout is investigated. According to the λ norm and expectation algorithm, the convergence condition of the system is derived. At last, simulation example shows the effectiveness and superiority of the presented method.